Perkembangan dan Tantangan Pasar Modal Indonesia - Niko Saputra; Jonatan Boyke A; Dedi Mulyadi (Peneliti.net, 2023)
The capital market is a place for companies to seek funds to finance their business activities. In addition, the capital market is also an effort to collect public funds directly by investing funds in healthy and well-managed companies. The main function of the capital market is as a means of capital formation and accumulation of funds for financing a company/issuer. The presence of capital market institutions in Indonesia adds a row of alternatives for people who have excess funds and are interested in investing to invest their funds This paper attempts to explain how the development of investment in the capital market, besides that this paper tries to describe some of the risks that have the potential to occur in investing in the capital market.